Migration and Asylum Flows to Germany: New Insights Into the Motives - Nowak-Lehmann, Felicitas (2021)
This study analyzes the determinants of both total migration and asylum migration to Germany. For the analysis, a comprehensive empirical model is set up that includes climate change, economic opportunities, such as per capita income differentials, links to Germany, home country characteristics (population growth, poverty, consumer confidence, unemployment), the political and institutional situation in the sending countries (measured by internal and external conflict, ethnic and religious tensions, government stability, law and order, military in politics), and a control for migration opportunities to alternative destinations. Panel data techniques (Poisson pseudo-maximum likelihood) for the estimation of the parameters of interest are employed using a panel of 115 (134) origin countries for asylum migration (total migration) over the period of 1996–2017 or 2001–2017, depending on data availability. The analysis reveals that political, socioeconomic, and economic factors determine both total migration and asylum migration. Economic factors are also determinants of asylum applications, as asylum seekers most often come for several reasons. Poverty plays a distinct role in total migration and asylum migration. An alleviation of poverty in origin countries is associated with less overall migration to Germany but with more asylum migration. Increases in average temperature also impact asylum migration in the expected direction, thus, increasing forced migration. The most interesting findings are revealed when considering country groupings (main migration countries, major asylum countries, countries whose asylum applicants enjoy high, intermediate, or low recognition rates).